PENGARUH MODEL PEMBELAJARAN NHT INTEGRATED TERHADAP KEMAMPUAN BERPIKIR KREATIF DENGAN MENGONTROL KEMAMPUAN AWAL SISWA - Nice Anggraini; syamsurizal syamsurizal; jefri marzal (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aims to see the effect of the NHT Integrated learning model on the ability to think creatively by controlling students' initial abilities. The method used is an experiment with anacova quantitative approach. The population is all students of class VII MTS. The sampling technique used by simple random sampling with 3 classes of samples. In the experimental class using the NHT integrated learning model and the control class using conventional NHT learning models. Data were collected using written test techniques, data analysis techniques in hypothesis testing using ancova with 3 x 1 factorial and continued with further testing. Based on the results of the study it can be concluded that (1) There is an influence of the NHT integrated learning model on the ability to think creatively by controlling the early ability of mathematics. Given the value of Fcount = 8.96> Ftable 3.15 and significance of SPSS 0.000 compared to the value of α (0.05) then 0.000 <0.05 and the hypothesis is accepted. (2) There is a different effect of NHT integrated learning model on the ability to think creatively by controlling the initial ability of mathematics. With the value of Fcount = 49.192> Ftable 3.15 and the significance of SPSS 0.000 when compared with the value of α (0.05) then 0.000 <0.05 and the hypothesis is accepted. This difference is seen in the significance level of SPSS 0.001 <0.05, which means that the learning model in the experimental class is better than the control class learning model.